Answer:
9 hours Cathy study per week
Step-by-step explanation:
=> according to the question
➪ x+2x-3=23
➪ 3x-3=24
➪ 3x=24+3
➪ 3x=27
➪ x= 27/3
➪ x= 9
ATQ
An exponent, or a power, is mathematical shorthand for repeated multiplications. An example of a power with an exponent of 3 is 2³, which equals 8.
An exponent, or a power, is mathematical shorthand for repeated multiplications. For example, the exponent "2" means to multiply the base for that exponent by itself.
So, for an exponent of 3, the base would be multiplied by itself three times.
An example of a power with an exponent of 3 would be 2³. This means that you need to multiply the base, which is 2, by itself three times: 2 x 2 x 2 = 8.
For more such questions on power, click on:
#SPJ1
The probable question may be:
What is the definition of powers in mathematics, and can you provide an example of a power with an exponent of 3?
Answer:
1) one muffin costs $1.50
one quart of milk costs $3.00
2) 10 videos, 30 CDs
Step-by-step explanation:
1)
m = cost of one muffin
q = cost of one quart of milk
System of equations:
3m + 1q = 7.5
8m + 2q = 18
I multiplied the first equation by -2 to eliminate the 'q' values
-6m - 2q = -15
+ 8m + 2q = 18
2m = 3
m = 3/2
find 'q':
3(3/2) + q = 7.5
9/2 + q = 15/2
q = 6/2 or 3
2)
c = # of CDs sold
v = # of videos sold
System of equations:
c + v = 40
4c + 6v = 180
I solved first equation for 'c' to get c = 40 - v
4(40-v) + 6v = 180
160 - 4v + 6v = 180
2v = 20
v = 10
10 + c = 40
c = 30
Answer:
4150
Step-by-step explanation:
a. $7.00
b. $15.50
c. $15.75
d. $16.50
Its 16.50
11.75 + 4.75
add them and you have your answer :) hope that helped
AN
x = 11.6
y = 11.6
= 11.6
y= 23.2
x = 18.3
y = 36.6
Answer:
(C)x=11.6, y=23.2
Step-by-step explanation:
Using Theorem of Intersecting Secant and Tangent
Applying this theorem in the diagram, we have:
Next, we apply Theorem of Intersecting Chords
PV X VQ=SV X VR
4 X x= 2 X y
Recall earlier we got: x=11.6
2y=4 X 11.6
2y=46.4
Divide both sides by 2
y=46.4/2=23.2
Therefore: x=11.6, y=23.2
multiplying polynomials find the product (2a-1)(8a-5)
The product of (2a-1)(8a-5) is 16a² - 18a + 5.
To find the product of (2a-1)(8a-5), we can use the distributiveproperty. This means that we multiply each term in the first polynomial (2a-1) by each term in the second polynomial (8a-5) and then combine like terms.
Applying the distributive property, we have:
(2a-1)(8a-5) = 2a(8a) + 2a(-5) - 1(8a) - 1(-5)
Simplifying this expression, we get:
16a² - 10a - 8a + 5
Combining liketerms, we have:
16a² - 18a + 5
Therefore, the product of (2a-1)(8a-5) is 16a² - 18a + 5.
In this case, we multiplied each term of the first polynomial by each term of the second polynomial, resulting in four terms. Then, we combined like terms to simplify the expression. The final product is a quadratic polynomial with a leading coefficient of 16 and terms involving the variable 'a'.
To learn more about Polynomials;
#SPJ6